Phenytoin as seizure prophylaxis in hematopoietic stem cell transplantation with busulfan conditioning - Germeraad, R. S.; Demandt, A. M. P.; Rouhl, R. P. W. (Frontiers in Neurology, 2022)
BACKGROUND - Phenytoin is widely used as primary seizure prophylaxis in hematopoietic stem cell transplantation in patients undergoing myeloablative conditioning with busulfan. Because of negative side effects of phenytoin, we abandoned phenytoin use in these patients. To assess the effect of this change, we performed a retrospective cohort study in all patients receiving busulfan. METHODS - We included 139 patients who underwent conditioning with busulfan for hematopoietic stem cell therapy. We registered the use of phenytoin as well as the occurrence of seizures until 7 days after busulfan administration. We compared seizure incidence between patients who received phenytoin and those who did not. RESULTS - Of the 43 patients who received phenytoin prophylaxis, 4 patients (9.3%) had a seizure during the conditioning regimen, of which 2 patients had a cerebral non-Hodgkin lymphoma. Furthermore, all these 4 patients had too high levels of phenytoin (intoxication). Of the 96 patients that did not receive phenytoin prophylaxis 3 patients (3.1%) had a seizure, 1 of these patients had an undefined cerebral lesion. Phenytoin did not relate to seizure prevention in a logistic regression analysis. CONCLUSION - We conclude that phenytoin prophylaxis in busulfan treated patients is obsolete, and possibly harmful, as phenytoin intoxication can occur. We recommend to discontinue the use of phenytoin as primary seizure prophylaxis in these patients.